MANUFACTURE OF PLANT GROWTH REGULATORS FROM ORGANIC MATERIALS USING BANANA PITH, COCONUT WATER, AND SPROUTS TO IMPROVE PLANT GROWTH PRODUCTIVITY - Fardha, Rizka (CV. Lafadz Jaya, 2024)
This article discusses the use of natural Plant Growth Regulators (PGRs) in accelerating plant growth. PGRs are synthetic chemicals that mimic endogenous plant hormones. However, due to their high cost, developing independent PGRs from organic materials presents an attractive alternative. Various organic materials containing plant hormones can effectively facilitate plant growth and development. This article uses a qualitative approach based on relevant literature on plant hormones and PGRs, focusing on banana pith and coconut water extracts. Results indicate that soaking mung beans in a 75% coconut water solution (A2B3) yields optimal growth. The article elaborates on five primary groups of PGRs—auxins, cytokinins, gibberellins, ethylene, and abscisic acid—and their roles and activation mechanisms in plants. It provides insights into the benefits of natural PGRs in supporting organic farming within home environments.